2017
DOI: 10.1111/jeb.13211
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and diet affect resistance, survival, and fecundity but not fecundity tolerance

Abstract: Insects are exposed to a variety of potential pathogens in their environment, many of which can severely impact fitness and health. Consequently, hosts have evolved resistance and tolerance strategies to suppress or cope with infections. Hosts utilizing resistance improve fitness by clearing or reducing pathogen loads, and hosts utilizing tolerance reduce harmful fitness effects per pathogen load. To understand variation in, and selective pressures on, resistance and tolerance, we asked to what degree they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 70 publications
(141 reference statements)
3
30
0
Order By: Relevance
“…Apart from mating, nutrients can influence female immune defences. In D. melanogaster flies, for example, females infected with bacteria survived better when fed a low amount of sugar or an added-yeast diet than when fed a high amount of sugar (Howick & Lazzaro, 2014) or a reduced-yeast diet (Kutzer et al, 2018). In several insect species, males provide a nuptial gift at mating, including prey items, secretions from male glands, and substances transferred in ejaculates (Thornhill & Alcock, 1983;Vahed, 1998;Gwynne, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from mating, nutrients can influence female immune defences. In D. melanogaster flies, for example, females infected with bacteria survived better when fed a low amount of sugar or an added-yeast diet than when fed a high amount of sugar (Howick & Lazzaro, 2014) or a reduced-yeast diet (Kutzer et al, 2018). In several insect species, males provide a nuptial gift at mating, including prey items, secretions from male glands, and substances transferred in ejaculates (Thornhill & Alcock, 1983;Vahed, 1998;Gwynne, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa as a pathogen. The effect of mating on female immune function is likely to depend on the pathogenic strain or species used (Short & Lazzaro, 2010) and genetic variation in host resistance (e.g., Tinsley et al, 2006;Kutzer et al, 2018). Short et al (2012) only used Pr.…”
Section: Post-mating Immune Functionmentioning
confidence: 99%
“…Genetic variation for tolerance is well established in animal systems (e.g., Blanchet, Rey, & Loot, ; Graham et al., ; Howick & Lazzaro, ; Parker, Garcia, & Gerardo, ; Råberg et al., ; Sternberg, Li, Wang, Gowler, & de Roode, ), but this is the first time that we have observed such variation for range tolerance in our infection system. This could be due to larger sample sizes than in a previous experiment, the fact that each genotype was selected specifically because they appeared to differ in disease tolerance and resistance, or other experimental design differences (Kutzer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For an overview of the experimental designs, see Figure . The lines were selected based on the results of a previous experiment (Kutzer, Kurtz, & Armitage, ), where we found that each varied in fecundity and in their capacity to resist bacteria. The stocks were maintained by placing adults onto new food every 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation